In vitro antimicrobial susceptibility of penicillinase-producing and intrinsically resistant Neisseria gonorrhoeae strains. - Cohen, M S (1983)
The in vitro susceptibility of penicillinase-producing and intrinsically resistant Neisseria gonorrhoeae strains to 13 antimicrobial agents was tested. Regardless of the type of resistance, these organisms remained quite susceptible to newer cephalosporin agents, including moxalactam, cefoperazone, cefotaxime, and ceftazidime.